2016
DOI: 10.1021/acsbiomaterials.5b00458
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Molecules Lower Catabolic Expression and Prevent Chondroitin Sulfate Degradation in an Osteoarthritic ex Vivo Model

Abstract: Aggrecan, the major proteoglycan in cartilage, serves to protect cartilage tissue from damage and degradation during the progression of osteoarthritis (OA). In cartilage extracellular matrix (ECM) aggrecan exists in an aggregate composed of several aggrecan molecules that bind to a single filament of hyaluronan. Each molecule of aggrecan is composed of a protein core and glycosaminoglycan sides chains, the latter of which provides cartilage with the ability to retain water and resist compressive loads. During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…A number of studies have investigated the diffusion of molecules into the articular cartilage ECM as treatments or drug delivery vehicles . Work done by other groups demonstrated diffusion of a positively charged molecule (66 kDa avidin ex vivo and in vivo) a large neutral molecule (500 kDa dextran ex vivo), and antibodies (150 kDa goat‐anti‐mouse antibodies ex vivo) into articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have investigated the diffusion of molecules into the articular cartilage ECM as treatments or drug delivery vehicles . Work done by other groups demonstrated diffusion of a positively charged molecule (66 kDa avidin ex vivo and in vivo) a large neutral molecule (500 kDa dextran ex vivo), and antibodies (150 kDa goat‐anti‐mouse antibodies ex vivo) into articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…This peptidoglycan aggrecan mimetic (mAGC) containing CS chains with attached HABPs replicated the HA-binding properties of native aggrecan ensuring that GAG localization was maintained within the scaffold. [204] mAGC had superior water regain properties to that of native aggrecan and mAGC constructs had superior compressive strength (78% increase), The catabolism of mAGC constructs by MMP-13 and ADAMTS-5 [206,207] was also reduced compared to in animal models of OA. AFM demonstrated that the attached peptide chains in mAGC assumed bottle-brush-type orientations on the CS-core structure similar to the CS chain arrangements in native aggrecan core protein.…”
Section: Production Of Biomimetic Neo-aggrecanmentioning
confidence: 96%
“…[205] Furthermore, localization of mAGC in the scaffold also stimulated synthesis of type II collagen. [206,208] A peptidoglycan lubricin-mimetic, mLUB15 has also been prepared by similar methodology to that of mAGC using HA binding peptide (GAHWQFNALTVRGGGC) and a type II collagen binding peptide (WYRGRL) attached to the CS backbone [209] (Figure 11b). [204] mAGC had superior water regain properties to that of native aggrecan and mAGC constructs had superior compressive strength (78% increase), The catabolism of mAGC constructs by MMP-13 and ADAMTS-5 [206,207] was also reduced compared to in animal models of OA.…”
Section: Production Of Biomimetic Neo-aggrecanmentioning
confidence: 99%
See 1 more Smart Citation
“…We (Phillips et al, 2018;Prudnikova et al, 2017;Prudnikova et al, 2018;Sarkar, 2011;Sarkar et al, 2017;Sarkar, Lightfoot-Vidal, Schauer, Vresilovic, & Marcolongo, 2012) and others (Bernhard & Panitch, 2012;Place, Kelly, & Kipper, 2014;Sharma, Panitch, & Neu, 2013;Sharma, Vazquez-Portalatin, Calve, & Panitch, 2016) have been investigating mimics to proteoglycans. We designed, synthesized and characterized biomimetic proteoglycans (BPGs) that mimic the molecular architecture and physical properties of natural proteoglycans.…”
Section: Hartmannmentioning
confidence: 99%